KETIDAKPASTIAN HUKUM DAN REGULASI TUMPANG TINDIH: IMPLIKASI TERHADAP PENEGAKAN HUKUM DAN PERTUMBUHAN INVESTASI DI INDONESIA - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study examines the issue of legal uncertainty arising from overlapping regulations in Indonesia and its implications for law enforcement and investment growth. As a country based on the rule of law, Indonesia is required to create legal certainty as the basis for justice, order and economic stability. However, in reality, legal practice in Indonesia is still marred by regulatory conflicts, both vertically between the central and regional governments and horizontally between ministries or sectors. This situation makes it difficult for law enforcement officials to interpret and apply the law consistently, leading to inconsistent decisions, weakening the legitimacy of the law, and opening up opportunities for abuse of authority. From an economic perspective, legal uncertainty has proven to have a negative impact on the investment climate. Investors bear high compliance costs, face delays in project implementation, and risk becoming entangled in protracted legal disputes. Furthermore, Indonesia's reputation in the eyes of global investors is undermined by its image of complex, unsynchronised, and frequently changing regulations. As a result, investment flows tend to weaken or shift to other countries that are considered to provide greater legal certainty, thereby hampering national economic growth and job creation opportunities. Using a qualitative approach with normative and empirical legal analysis, this study emphasises that regulatory harmonisation and legislative governance reform are urgent necessities for achieving legal certainty that supports fairer law enforcement and a more conducive investment climate. The results of this study are expected to contribute to legal reform efforts in Indonesia, particularly in creating a credible, efficient, and globally competitive legal system.